Urinary tract infection in children - Monika Kusz; Adam Alzubedi; Agnieszka Maślak; Paulina Pawluczuk; Paweł Polski (Kazimierz Wielki University, 2020)
Urinary tract infections are considered to be one of the most common bacterial infection in children. In 30 % of children with anomalies of urinary tract , urinary tract infection (UTI) can be the first sign. UTIs are classified according to site, symptoms or episode. E. coli is responsible for 80-90 % of acute pyelonephritis episodes. Symptoms include fever, dysuria, tenderness in the lower abdomen are typical for older children, whereas for younger are non-specific. Diagnosis is based on clinical symptoms, abnormal urine analysis and growth on urine culture. Urine culture is still a gold standard for diagnosing urinary tract infections. Antibiotics are usually effective, although antibiotics resistance is still an increasing problem.